2021
DOI: 10.1371/journal.pone.0248762
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of financial incentives to improve glycemic control in adults with diabetes: A pilot randomized controlled trial

Abstract: Purpose Determine the cost-effectiveness of three financial incentive structures in obtaining a 1% within group drop in HbA1c among adults with diabetes. Methods 60 African Americans with type 2 diabetes were randomized to one of three financial incentive structures and followed for 3-months. Group 1 (low frequency) received a single incentive for absolute HbA1c reduction, Group 2 (moderate frequency) received a two-part incentive for home testing of glucose and absolute HbA1c reduction and Group 3 (high fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“… 10 Siegel et al, in their systematic review, concluded that MDT interventions for T2DM patients and proper glycemic control are highly cost-effective ($11,339/QALY) in comparison with usual care. 40 Moreover, Egede et al 42 suggested Incremental cost-effectiveness ratios (ICERs) of $1000-$4000 per 1% reduction in HbA1c among multi-component diabetes interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 Siegel et al, in their systematic review, concluded that MDT interventions for T2DM patients and proper glycemic control are highly cost-effective ($11,339/QALY) in comparison with usual care. 40 Moreover, Egede et al 42 suggested Incremental cost-effectiveness ratios (ICERs) of $1000-$4000 per 1% reduction in HbA1c among multi-component diabetes interventions.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no significant difference in the costs of in-patient hospitalizations due to cardiovascular or microvascular complications. 10 40 Moreover, Egede et al 42 suggested Incremental costeffectiveness ratios (ICERs) of $1000-$4000 per 1% reduction in HbA1c among multi-component diabetes interventions.…”
Section: Discussionmentioning
confidence: 99%
“…All three arms received proven effective strategies for improving blood glucose management, including basic diabetes education with goal setting, which has been shown to improve HbA1c. 37 Although both financial incentives and CHW support have previously been shown to be cost-effective strategies 38 , 39 that improve diabetes outcomes 14 , 15 , 35 but have not been studied in combination. Over 80% of participants in the hybrid arm demonstrated low adherence or high blood glucose levels, even with the digital health intervention, and were thus “escalated” to receive CHW support.…”
Section: Discussionmentioning
confidence: 99%